2011
DOI: 10.1016/j.jhealeco.2011.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Does better disease management in primary care reduce hospital costs? Evidence from English primary care

Abstract: We apply cross-sectional and panel data methods to a database of 5 million patients in 8,000English general practices to examine whether better primary care management of 10 chronic diseases is associated with reduced hospital costs. We find that only primary care performance in stroke care is associated with lower hospital costs. Our results suggest that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 32 publications
2
50
0
1
Order By: Relevance
“…In studies of the UK Quality and Outcomes Framework, in which incentives were directly tied to measured quality of care, any observed decreases in hospital admissions accompanying observed changes in quality were small, [25][26][27] and some studies found no association between measured quality and hospital admissions. 28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of the UK Quality and Outcomes Framework, in which incentives were directly tied to measured quality of care, any observed decreases in hospital admissions accompanying observed changes in quality were small, [25][26][27] and some studies found no association between measured quality and hospital admissions. 28,29 Research to date, largely from the United Kingdom and United States, has provided mixed evidence of the effectiveness of these programs.…”
Section: Discussionmentioning
confidence: 99%
“…39 Most research in this area focuses on care for individual diseases, using the delivery of specific services as indicators of quality. 24,[30][31][32][33][34] Evidence of the effect of incentive-based programs on broader outcomes such as access to primary care, continuity of care, 40 hospital admissions [25][26][27][28][29]41,42 and overall resource use 30,34,43 has been inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it must be shown that such a fee gap exists, conditional on doctors' quality. Quality is not observed, however the literature (e.g., Dusheiko et al, 2011) has used a doctor's participation chronic disease management programs as an indicator for quality primary care. This is also consistent with the hospital performance literature (e.g., Geweke, 2003) in which high quality hospitals are often observed to have poor performance, like higher mortality rate, because they tend to attract sicker/more complex patients.…”
Section: Methodsmentioning
confidence: 99%
“…Secondly, our work adds to the literature that studies whether the strengthened role of primary care policies and GPs can foster a more appropriate utilisation of hospital services by containing admission rates (e.g. Dusheiko et al, 2011;McCormick and Nicodemo, 2014).…”
Section: Introductionmentioning
confidence: 98%